Developing a competency framework for extracorporeal membrane oxygenation nurses: A qualitative study - Liwei Hong; Chunyi Hou; Lihua Chen; Xiaoqun Huang; Jingye Huang; Weijuan Liu; Xiangxiang Shen (Wiley, 2023)
Abstract Aim To develop a competency framework applicable to Chinese extracorporeal membrane oxygenation (ECMO) nurses. Design A qualitative study was performed following the consolidated criteria for reporting qualitative research. Methods Semi‐structured interviews based on the critical incident technique were conducted among 21 ECMO care providers recruited from five well‐known ECMO centres in Guangzhou, China. Interview transcripts were coded and analysed using the constant comparative method. The data collection period lasted from November 2021 to April 2022. Results A competency framework for ECMO nurses was identified. It included four domains: knowledge, skills, behaviours and attitudes, containing 33 subcompetencies and 66 items. Relevance to clinical practice This framework can be a reference for the assessment and training of ECMO nurses.